Value Chain Analysis on the Logistics Management as the Basis for Strategy Formulation to Increase Customer Satisfaction (Case Study in PT.Coca-Cola Amatil Indonesia - Plant East Java) - Dian Setyawati; Imam Santoso; Mas’ud Effendi (Agroindustrial Journal, 2017)
PT. Coca-Cola Amatil Indonesia (PT. CCAI) - Plant East Java as a carbonated soft drinks manufacturer isexperiencing a mismatch between planning and realization of product shipments shown by fullfilment anddelivery mismatch among the company target at difotai (delivery infull ontime accurately invoice). This thingwas d ue to an incompatibility among logistics management activities, so it is necessary to do value chainanalysis to find out which activity is the cause of nonconformities in order to do strategy formulationimprovement to enhance customer satisfaction. The purpose of this study was to determine the advantagesand disadvantages of logistics management in PT.CCAI - Plant East Java and make it as one of the basis forstrategy formulation to improve customer satisfaction with value chain analysis approach. This researchused descriptive analytical method. The data was obtained by distributing questionnaires to the Warehouseand Transportation in PT. CCAI - Plant East Java and analysed using fuzzy AHP method. The resultsshowed that the overall weight of the main activities in a row from the top was the activity of supplymanagement, information flow and order processing, demand planning and operations, and transportation.Some things on the transportation activities that needed to be improved as the basis for the strategyformulation, among others, operational procedure, the carrying capacity of the facility, as well as thesocialization and communication of problems and changes handling.